A methodology for identifying time-trend patterns - Košmelj, Katarina (Metodološki zvezki, 2008)
The aim of our study is to reveal different time-trend patterns in the ratio of advertising expenditure to gross domestic product for 28 European countries in the 1994-2004 period. To fulfil the objective, we applied two multidimensional statistical approaches: cluster analysis and multidimensional scaling for time-varying data, followed by linear regression analysis of the time-series within the clusters. A proximity matrix was calculated using the dissimilarity between two time series, which takes into account the order of time points, the information on the fixed time points, and the weights. We identified four clusters of countries with similar trend patterns in the 1994-2004 period: awakening countries, stable countries, catching-up countries, and the leading cluster.
Keywords: Europe; Evropa; propaganda; stroški; trendi; statistične metode; časovne vrste